2009
DOI: 10.4049/jimmunol.0803544
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptor Proteins and Ras Synergistically Regulate IL-1-Induced ADAMTS-4 Expression in Human Chondrocytes

Abstract: Aggrecanases (a dystrophin and metalloproteinase with thrombospondin motif, ADAMTSs) are principal proteases involved in cartilage extracellular matrix aggrecan degradation. The role and relative contribution of MyD88, IRAK1, and TRAF6 adaptor proteins in IL-1β regulation of aggrecanase-1 (ADAMTS-4) is unknown. By small interfering RNAs-mediated knockdown, we show that IL-1β-induced up-regulation of ADAMTS-4 in chondrocytes requires MyD88, IRAK1, and TRAF6 adaptor proteins. However, partial inhibition of ADAMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 62 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…It was recently reported that IL-1␤-induced dystrophin and metalloproteinase with thrombospondin motif (ADAMTS)-4 upregulation was only partially inhibited by the knockdown of MyD88, IRAK1, and TNF receptor-associated factor (TRAF)6 (Ahmad et al 2009), suggesting the existence of a MyD88-independent pathway in IL-1R-mediated signaling. In the present study, PKC␦ was phosphorylated by IL-1␤ in human alveolar epithelial cells ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It was recently reported that IL-1␤-induced dystrophin and metalloproteinase with thrombospondin motif (ADAMTS)-4 upregulation was only partially inhibited by the knockdown of MyD88, IRAK1, and TNF receptor-associated factor (TRAF)6 (Ahmad et al 2009), suggesting the existence of a MyD88-independent pathway in IL-1R-mediated signaling. In the present study, PKC␦ was phosphorylated by IL-1␤ in human alveolar epithelial cells ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)‐4 and ADAMTS‐5, also referred to as aggrecanase‐1 and aggrecanase‐2, are principally responsible for aggrecan degradation in degenerative cartilage diseases. In human osteoarthritis, both ADAMTS‐4 and ADAMTS‐5 are expressed and ADAMTS‐4 is regulated by IL‐1 and TNF‐α [102,103]. In human synoviocytes, expression of ADAMTS‐4 but not ADAMTS‐5 is suppressed by inhibition of TNF‐α or IL‐1β signaling by the TNF‐α blocker Ethernacept or neutralizing IL‐1β antibodies, respectively [102].…”
Section: Anabolic and Catabolic Factorsmentioning
confidence: 99%
“…Furthermore, treatment with oncostatin M and either IL-1β or TNF-α in human chondrocytes or cartilage explants, leads to a marked induction of ADAMTS-4 with a lesser upregulation of ADAMTS-5 (Song et al, 2007). This process seems to be mediated by Ras signaling (Ahmad et al, 2009). Additionally, some data demonstrate that only ADAMTS-4 levels are increased in OA cartilage (Malfait et al, 2002; Roach et al, 2005; Naito et al, 2007).…”
Section: Aggrecanasesmentioning
confidence: 99%